Coat colour pattern in Garut sheep and its crossbred - Ismeth Inounu; D. Ambarawati; R.H. Mulyono (Indonesian Center for Animal Research and Development (ICARD), 2009)
Coat colour is a qualitative trait whose expression is controlled by genes and could be used as a characteristic of sheep breed and could be used as a trade mark for certain sheep breeder enterprise. The research was done to study the coat color pattern in Garut sheep and its crossbred. In this study 178 heads of sheep was used which consisted of 64 Garut sheep (GG); 24 MG sheep (50% M and 50% G); 14 HG sheep (50% St. Croix and 50% G); 20 HMG sheep and 56 MHG sheep. HMG and MHG sheep are compost of 25% St Croix; 25% M. Charolais and 50% Garut. Phenotypic observation of coat colour were done by visualization and from the picture of sheep as individual identity in each position from the right; the left, front and rear sites. Sheep coat colour pattern in this study was largely determined by 5 main alleles: white or tan (65.7%), wild (17.4%), badgerface (14.6%), Light badgerface (0.6%) and black and tan (1.7%) that present at the Agouti locus. Other locus that determine the coat colour pattern in this study are Albino (C); Australian Piebald (AsP); Brown (B); Extension (E); Pigment Head (Ph); Roan (Rn); Spotting (S); Sur Bukhara and Sur Surkhandarya (SuB/SuS) and Ticking (Ti) all of these locus increase the variation of coat colour pattern. Key words: Coat Colour Pattern